Socioeconomic impacts of drug and substance abuse on secondary school students in Nigeria from 1980 to 2023: A narrative review of the extent of published studies - Christopher O, Kwokori; Brian O, Ogbonna; Maureen U, Anetoh; Sonne I, Mbagwu; Ogochukwu F, Offu (Journal of Community Medicine and Health Solutions, 2023)
Background: The socioeconomic impact of drug and substance abuse on secondary school students in Nigeria is yet to be fully evaluated even in the face of the current surge in abuse of substances among the younger folks who constitute more than half of the entire population. Objective: This study narratively reviewed the studies on the socioeconomic impacts of drug and substance abuse on secondary school students and studies by researchers in Nigeria. Methods: The study was a narrative review of the literature covering the socioeconomic impacts of drug and substance abuse on secondary school students in Nigeria from 1980 to 2023. Data were extracted and summarized with descriptive statistics. Results: All the studies took place between 2012 and 2023; 6 (100%). The studies carried out were all observational studies 6 (100%). All the studies fell below average in the benchmark for the hierarchy of evidence-based studies. The studies mostly took place in the South-West 3 (50.00%), while 1 (16.67%) took place in the South-East, North-West, and North-Central respective regions of Nigeria. Conclusion: The available studies done on the impacts of drug and substance abuse focused more on the social impacts, with little or no attention to the economic effect. The available studies however remain at the observational level in the evidence-based ladder. Future Research on the reviewed theme should focus on the economic implications of the social effects of drug and substance abuse on secondary school students in Nigeria.